(untitled) (Bulletin of Kharkiv National University of Internal Affairs, 2021)
Topical issues of certification of police officers have been considered. The approaches of scientists to the definition of such concepts as "certification" of police officers have been studied. The views of scientists on the institute of certification, its legal regulation and the expediency of conducting have been analyzed. The history of the certification procedure and the grounds for its application have been considered, the main characteristics of the attestation and types have been clarified. The purpose of certification is seen in the most rational use of personnel, increasing the efficiency of their work. It was found that the definition of "certification" of police officers was first enshrined in law during the reform of the law enforcement system. Certification of police officers is enshrined in the new Law of Ukraine "On the National Police" from July 2, 2015 № 580-VIII, on the basis of which a new body was established, that is the police. Police certification is considered a professional standard and one of the important criteria in police service. Certification has no periodicity and has a special subject. We consider the desire for openness and transparency of its conduct to be positive in the police certification procedure. Three types of police certification have been studied. An exhaustive list of types of certification has been established. Based on the analysis of the legal regulation of the procedure of certification of police and scientific views of scientists, the definition of " certification " has been defined and characterized. The materials of the judicial practice on appealing the decisions of the certification commissions of the National Police bodies on dismissal of police officers as a result of their failure to pass the certification in Ukraine have been studied. The current state of legal regulation of the procedure of certification of police officers in Ukraine has been analyzed, its positive and negative aspects have been clarified.